Knowledge, Attitude, and Practice of the Lebanese Community Toward COVID-19 - Domiati, Souraya; Itani, Mohamad; Itani, Ghida (Frontiers in Medicine, 2020)
.Objectives: Distinct measures were adopted in Lebanon to prohibit the spreading of SARS-CoV-2. These actions provide positive results only if the population chooses to be compliant. Aim Accordingly, this study aimed to reflect the Lebanese population adherence by determining their level of knowledge and practice during this pandemic. Method: A cross-sectional online survey was performed in April 2020. It involved 410 volunteers from the main 5 Lebanese districts. The questionnaire was divided into 3 parts; sociodemographic, knowledge, and practice. A score was made from 18 points to evaluate the knowledge of the respondents. The last 8 questions reflected the participants’ precautionary methods during the pandemic. Descriptive statistics and one-way analysis of variance tests were conducted using SPSS version 20. Results: The overall correct rate of the knowledge questionnaire was 75%. Survey completers of extreme age groups (under 18 and >44), elementary education level, and medical occupation displayed the least level of knowledge compared to other groups (p-value<0.05). Most of the participants showed proactive practices to protect themselves against COVID-19. They covered their mouth (81.2%), threw the used tissue (93.7%), and washed their hands (66.6%) after sneezing or coughing. Moreover, they wear face masks if they were sick (59%) or in a crowded place (79.3%). Concerning Hydroxychloroquine, 10% claimed that they would take it if they have COVID-19 symptoms. Conclusion: This survey sheds light on the fact that one mandatory measure does not fit all the population, there must be a specialized method of prevention for each profession, age group, and area of the country to prevent the outbreak of COVID-19.